Foam as a complex system - WEAIRE, DENIS; HUTZLER, STEFAN (My University, 2009)
What is a `complex system?? The two-dimensional foam, as originally popularized by Cyril Stanley Smith, provides an ideal context in which to explore this question.
PUBLISHED
Keywords: Condensed matter physics; dimensional foam; Nanoscience & Materials